“I Feel I Can Work for a Long Time…” Interview with Stanislav Mikhailovich Grigoriev before His Anniversary - Marina Tkacheva (Proekt Bajkal, 2015)
Stanislav Grigoriev is one of the actively practicing architects of the 1960s generation. His biography and creative career, professional principles and the most famous realizations are presented.